Multilingualism in the Teaching and Learning of Accounting in Chris Hani West District, South Africa - Avela Ngqunguza; Zikhona Seleke (Journal of Education and Learning Technology)
This study investigated the effectiveness of employing multilingualism in the teaching and learning of accounting in secondary schools within the Chris Hani West District, South Africa. The primary purpose was to assess whether multilingual approaches enhance or impede the educational experience in accounting classrooms. A qualitative research methodology was adopted, involving interviews conducted across three high schools in the district. Participants included teachers and learners, providing diverse perspectives on implementing multilingualism in accounting education. Findings revealed mixed opinions regarding the use of multiple languages in instruction. While multilingualism was found to promote increased participation and enjoyment among learners, it also posed challenges, such as extended instructional time due to code-switching and a greater emphasis on linguistic skills over subject content. Teachers expressed concerns about the additional time required to effectively employ multiple languages, which could detract from covering essential accounting concepts. The study recommends that the Department of Education, policymakers, and relevant stakeholders develop and implement inclusive education strategies that address language barriers without marginalizing any learners. This includes providing support and resources for teachers to effectively manage multilingual classrooms and ensuring that educational policies accommodate diverse linguistic needs. The study contributes to existing scholarship by highlighting the complex dynamics of multilingual education in accounting classrooms. These findings can inform future educational policies and teaching practices aimed at creating more inclusive and effective learning environments that leverage linguistic diversity as a resource rather than a hindrance.